Tracing the discursive development of rapport in intercultural nurse–patient interactions. (7th February 2017) - Crawford, Tonia; Roger, Peter; Candlin, Sally
Abstract : Good rapport underpins effective patient care; however, communication barriers can undermine the building of rapport and the development of a therapeutic relationship, potentially resulting in poorer health outcomes. This paper examines the development of rapport by registered nurses (RNs) from a variety of cultural and linguistic backgrounds. Discourse analytical techniques are used to trace rapport‐building in naturally occurring interactions through the course of the participants' nursing care. Ethnographic techniques including participant observations and audio‐recordings of interactions were conducted in Sydney, Australia, and analysed using interactional sociolinguistic (IS) and theme oriented discourse analytic approaches. This paper demonstrates how rapport is accomplished by the RNs through strategies such as humour, reassurance, small talk and use of colloquial language.